Effect of calcination temperatures on microstructure and phase formation of Ba(Zr0.25Ti0.75)O3 powders - Bongkarn, T.; Phungjitt, N.; Vittayakorn, N. (My University, 2008)
In this work, the effect of calcination temperatures on the microstructure and phase formation of Ba(Zr0.25Ti0.75)O3 (BZT) powders were investigated. The BZT powders were prepared via the solid state reaction method under various calcination temperatures. It was found that the second phases such as BaCO3 ZrO2, BaZrO3 and Ba2ZrO4 existed in samples with calcination temperature below 1200 °C. Homogeneity and a highly pure perovskite phase of the BZT powders were obtained with calcination condition at 1300 °C for 4 h. Lattice parameter a and the percentage of cubic perovskite phase tended to increase with increasing calcination temperatures. The TG-DTA results corresponded to the XRD investigation. The microstructures of calcined powders exhibited an almost-spherical morphology and had a porous agglomerated form in all samples. The average particle sizes were increased from 0.2 to 1.1 μm when calcination temperatures were increased from 800 to 1350 °C. © 2008 Trans Tech Publications, Switzerland.
Keywords: Barium zirconate titanate; Microstructure; Phase formation; Solid state reaction